Factors affecting surfacing, respiration, and dive behaviour of bowhead whales, Balaena mysticetus , summering in the Beaufort Sea - Dorsey, Eleanor M.; Richardson, W. John; Würsig, Bernd (Canadian Journal of Zoology, 1989)
Behaviour of bowhead whales summering in the Canadian Beaufort Sea in 1980–1984 was observed from an aeroplane circling at altitudes high enough to avoid disturbance (≥ 457 m). Factors that might affect surfacing and respiration behaviour were assessed with univariate and multivariate analyses. Calves (age < 1 year) were not considered. The interval between successive blows in a surfacing was more stable over time and over different activities than were the other variables but was significantly longer in surface-feeding whales. Surface feeders also made longer surfacings. The number of blows per surfacing and duration of surfacing were highly correlated, and both variables were more consistently correlated with the duration of the previous dive than with the duration of the subsequent dive. There were considerable interyear variations in respiration and surfacing characteristics that could not be attributed to any measured factor. Effects of water depth on number of blows per surfacing could not be separated from interyear effects, but duration of surfacing appeared to be greater in deeper water. Whales in groups had longer blow intervals, as did mothers with calves and socializing whales. Underwater blows were associated with socializing, at least at times, but their function is uncertain. The results have implications with regard to bowhead energetics, sightability during aerial surveys, and interpretation of behaviour in the presence of human disturbance.